Effectiveness of cognitive behavioral therapy with yoga in reducing job stress among university lecturers - Igu, Ntasiobi C. N.; Ogba, Francisca N.; Eze, Uchenna N.; Binuomote, Michael O.; Elom, Chinyere O.; Nwinyinya, Emeka; Ugwu, Joy I.; Ekeh, David O. (Frontiers in Psychology, 2023)
Abstract Job stress is highly prevalent in the workforce and tends to threaten employees’ physical and mental well-being, reducing organizational outcomes. The negative impacts of workplace stress on academics have been found to disproportionately interfere with both institutional research productivity and learning outcomes. This study analyzed data from a randomized control trial, to validate the effectiveness of cognitive behavioural therapy combined with yoga in treating job-related stress among lecturers from two Universities in South-East, Nigeria. Participants included 93 academic staff members from two Federal Universities in Enugu and Ebonyi States in Nigeria. We assigned participants to Y-CBT (N=46) and waitlist control (N=47) groups using random sampling techniques. A 2-hour Y-CBT program was delivered weekly for a period of 12 weeks. Two instruments were used to collect data for the study. Single Item Stress Questionnaire (SISQ) was employed to identify the potential participants, while the teachers’ Stress Inventory (TSI) was served for data collection at baseline, post-intervention, and follow-up tests. Mean, standard deviations, t-test, statistics, and repeated measures Analysis of Variance, were used to analyze data for the study. Results revealed that the perception of stressors and stress symptoms reduced significantly at post-test and follow-up assessments following Y-CBT intervention. The conclusion was that Y-CBT can minimize the perception of stressors and stress manifestation among university lecturers.